DETERMINATION OF SUGAR CONTENT IN WATER SOLUTIONS BY OPTICAL METHODS - FILIPEK, Josef (Trends in education, 2008)
The content of saccharose in water solution influences the value of index of refraction as well as plane of vibration turn of polarised light. This effect is used during measuring by refractometer and polarimeter. The author was demonstarting the principles of sugar content determination by use of refractometer and polarimeter.
Keywords: refractometer; polarimeter; limit angle; turn of plane of vibration; interactive animations